Solving ITC2007 examination timetabling problem by using simulated annealing - Tan, Wei Ren (2014)
The examination timetabling problem includes arranging the exams to certain or finite number of available rooms and timeslots, by the aim of fulfill the hard constraints and satisfy with the soft constraints as far as possible. In the literature, it has shown quite a few technique which has been applied to solve the simplified examination benchmark dataset, it can be found from the scientific literature. In this research, ITC 2007 (International Timetabling Competition 2007) examination track is been drawn. Quite a few of novel constraints are involved in this dataset. A total of 12 dataset which are having different kind of feature for example the number of exam, the number of the timeslot, the number of the room and room capacity. To solve the timetabling problem, Graph Heuristic and Simulated Annealing method Are been used on it. Which Graph Heuristic will be used to generate the initial solution and Simulated Annealing method will be used to improve the initial solution.